2022
DOI: 10.1029/2022je007286
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Structure of the Middle and Upper Atmosphere of Mars From ACS/TGO CO2Spectroscopy

Abstract: Temperature and density in the upper Martian atmosphere, above ∼100 km, are key diagnostic parameters to study processes of the species' escape, investigate the impact of solar activity, model the atmospheric circulation, and plan spacecraft descent or aerobraking maneuvers. In this paper, we report vertical profiling of carbon dioxide (CO2) density and temperature from the Atmospheric Chemistry Suite (ACS) solar occultations onboard the ExoMars Trace Gas Orbiter. A strong CO2 absorption band near 2.7 μm obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Additional seasonal effects that we exclude may add nuance. Studies have demonstrated variability in the height of the homopause (Belyaev et al., 2022; Slipski et al., 2018) and mesospheric temperature (Gupta et al., 2022; Jain et al., 2023; Slipski et al., 2018) throughout the martian year. If included in our model, enhancements in both of these parameters during the perihelion season would likely both slightly suppress the diffusion of H and resulting escape, competing with the escape enhancement caused by the extra supply of atoms in the mesosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Additional seasonal effects that we exclude may add nuance. Studies have demonstrated variability in the height of the homopause (Belyaev et al., 2022; Slipski et al., 2018) and mesospheric temperature (Gupta et al., 2022; Jain et al., 2023; Slipski et al., 2018) throughout the martian year. If included in our model, enhancements in both of these parameters during the perihelion season would likely both slightly suppress the diffusion of H and resulting escape, competing with the escape enhancement caused by the extra supply of atoms in the mesosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we expect that the variation of the height of the peak GW perturbations with solar longitude should be similar to the seasonal pattern of the wave turbopause. In fact, Belyaev et al (2022) found significant seasonal variability in the homopause due to the influence of atmospheric aerosol loading, rising from 90 to 100 km at aphelion to 120-130 km at perihelion. This is consistent with the seasonal variation characteristics of the height of the strongest GW perturbations, suggesting that GW activity has a very important influence on the thermal structure of the Martian middle atmosphere.…”
Section: Temporal Evolution Of Climatological Gwsmentioning
confidence: 99%
“…In this study, we directly used temperature data retrieved by Belyaev et al (2022) with ACS/MIR observations, including 568 vertical profiles. The time period is from 2018 May to 2021 January, corresponding to 1.5 Martian years (MYs), from L s = 181°for MY34 to L s = 355°for MY35.…”
Section: Tgo/acs Data and Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…The MIR spectrometer of the Atmospheric Chemistry Suite (ACS) experiment on board the Trace Gas Orbiter (TGO; Korablev et al 2018) allows for this gap in the knowledge of atmospheric variability to be filled by measuring vertical profiles of density and temperature between 20 and 160-180 km in the Martian atmosphere (Belyaev et al 2022). The algorithm of retrieving GW profiles and their characteristics, together with the first results of its application, have been presented in detail in the work by Starichenko et al (2021).…”
Section: Introductionmentioning
confidence: 99%